Improve Accreditation, Regulation, and Quality Standards : For Dignified, Person-Centered Care Amidst Demographic Change (World Bank, Washington, DC, 2019)
In mature health systems, emerging health innovations require an adaptive and robust regulatory regime, alongside accreditation standards that are useful to consumers, to scale effectively. New health care modalities, including mobile apps and telehealth, can help countries expand high-quality patient-centered care while responding to demographic changes. However, despite the potential usefulness of these innovative tools, most remain outside the scope of regulatory bodies, are not subject to quality or safety standards, and vary widely in their compliance with best practice. Inappropriate or misaligned regulatory regimes can also create unnecessary constraints to both cost-effective provision options such as telehealth, and also labor force mobility across sub-national and national borders.